Measurement of Mass Evaporation of Ni-based Single Crystal Super Alloy Using Electrostatic Levitation (ESL) and Electromagnetic Levitation (EML) - Nawer, Jannatun. (2018)
Abstract: Increasing usage of Nickel-based super alloys in aerospace, power plant and nuclear reactors has made it necessary to model fluid flow during casting process. It is crucial to measure thermo-physical properties of these alloys accurately for this modelling purpose. Ni-based single crystal super alloy CMSX-4 plus were investigated for mass evaporation to analyze the mass loss using Electro Static Levitation (ESL) method. Two models were developed to predict the mass loss & dynamic mass during each thermal cycle. The first model predicts the rate of mass evaporation in ideal case where the evaporation is maximum with a correction factor. The second model predicts the mass evaporation with a correction of Aluminum activity which was calculated by evaluating the results from elemental analysis for Al, Cr, Ti, and Co. Both the models were applied and compared with the data obtained from another super alloy CMSX-10K using ESL. The models were also applied to CMSX-10K processed in Electro Magnetic Levitation (EML) to compare its accuracy for different sample size. Both models are not viable for analyzing space data yielding significant error. The 2nd model predicts the mass evaporation for Al & Co within ±6 % errors for CMSX-4 plus samples processed in ESL.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Douglas Matson.; Committee: Iryna Zenyuk, and Robert Peattie.; Keywords: Mechanical engineering, and Materials Science.